2020
DOI: 10.4111/icu.2020.61.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from 12,000 robotic radical prostatectomies: Is the journey as important as the outcome?

Abstract: Robotic radical prostatectomy (RARP) is a standardized treatment for localized prostate cancer, which provides better functional outcomes and similar oncological outcomes compared to open approaches. Here, we share our experience of 12,000 RARPs by describing the outcomes of the procedure in terms of positive surgical margin (PSM), continence, and potency as well as by presenting our detailed surgical technique with recent modifications. On cancer control, the PSM rates were 5.8% and 26.1% in T2 and T3, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 62 publications
3
17
3
3
Order By: Relevance
“…The patients were discharged at an average of 16 h with no readmissions or post-discharge narcotic use. Early oncological and quality of life outcomes were also acceptable and compatible with our multiport experience [4]. After our initial learning curve, we would advise a cautious approach to SP RARP, the technology is quite revolutionary and has the potential to be very effective.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The patients were discharged at an average of 16 h with no readmissions or post-discharge narcotic use. Early oncological and quality of life outcomes were also acceptable and compatible with our multiport experience [4]. After our initial learning curve, we would advise a cautious approach to SP RARP, the technology is quite revolutionary and has the potential to be very effective.…”
Section: Discussionsupporting
confidence: 63%
“…We characterised the nerve sparing performed as bilateral full nerve sparing (patients who had a nerve preservation of ≥95%) and partial nerve sparing (patients who had 50–95% of nerve preservation) according to our technique classification described previously [4]. Full continence was defined as the use of no pads.…”
Section: Methodsmentioning
confidence: 99%
“…and less blood loss 19,20 . In our series, the overall PSM rate was 30.1%, which is a higher rate than that reported in high-volume RARP studies, in which the range typically was 10.8-22% 21 . This may be attributable to a much higher percentage (56.6%) of patients in the pT3 stage in our study than in other studies, where the percentage of pT3 stage patients ranged from 9.3 to 37.5% 21 .…”
Section: Effect Of Psms On Biochemical Recurrencecontrasting
confidence: 66%
“…Previous studies have been reported the apex is the most frequent region of PSM in RP specimens 31,41 . This is attributable to the unclear prostate capsular margins, which are di cult to identify in pT2 and pT3 stages 38 . More other studies have reported that apical PSM is correlated with the surgeon's approach and skills rather than the tumor stage 21,26,41 . The surgeon in this study has extensive laparoscopic experience, explaining the relatively low rate of PSM in the apex.…”
Section: Effect Of Psms On Biochemical Recurrencementioning
confidence: 95%
“…Needless to say, RARP needs to achieve not only cancer control, but also preserve urinary continence and erectile function. 1,2 Therefore, RARP has been considered a challenging operation, even today.…”
Section: Introductionmentioning
confidence: 99%